On the Review and Setup of Security Audit using Kali Linux - Teddy Surya Gunawan; Muhammad Kassim Lim; Nurul Fariza Zulkurnain; Mira Kartiwi (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The massive development of technology especially in computers, mobile devices, and networking has bring security issue forward as primarily concern. The computers and mobile devices connected to Internet are exposed to numerous threats and exploits. With the utilization of penetration testing, vulnerabilities of a system can be identified and simulated attack can be launched to determine how severe the vulnerabilities are. This paper reviewed some of the security concepts, including penetration testing, security analysis, and security audit. On the other hand, Kali Linux is the most popular penetration testing and security audit platform with advanced tools to detect any vulnerabilities uncovered in the target machine. For this purpose, Kali Linux setup and installation will be described in more details. Moreover, a method to install vulnerable server was also presented. Further research including simulated attacks to vulnerable server on both web and firewall system will be conducted.